2009
DOI: 10.3892/ijmm_00000194
|View full text |Cite
|
Sign up to set email alerts
|

Association between estrogen receptor α polymorphisms and equol production, and its relation to bone mass

Abstract: Abstract. To investigate the relationship between estrogen receptor polymorphisms and equol production and its effect on bone turnover, 139 workers (mean age 38.3±11.1 years) in Japan were recruited. Bone mineral density (BMD), bone turnover markers, and serum equol were measured at a health examination. DNA samples were prepared to detect the estrogen receptor · (ER·) polymorphism and were digested by PvuII. The number of equol producers was 57. No statistically significant differences were observed in bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…According to Do et al ( 2007 ), the daily intake of in natura soybean grains is 2.5 ± 4.9 g ( n = 708 ). In Asian countries—the largest consumers of soybean—the daily intake of soybean and soy-related foods is 23.0 ± 18.2 g (Toyomura and Kono, 2002 ; Do et al, 2007 ; Katsuyama et al, 2009 ). Thus, the amount of Ni in soybean grains found in this study is considered safe and does not pose a threat to human health if direct consumption of grain is taking into account.…”
Section: Discussionmentioning
confidence: 99%
“…According to Do et al ( 2007 ), the daily intake of in natura soybean grains is 2.5 ± 4.9 g ( n = 708 ). In Asian countries—the largest consumers of soybean—the daily intake of soybean and soy-related foods is 23.0 ± 18.2 g (Toyomura and Kono, 2002 ; Do et al, 2007 ; Katsuyama et al, 2009 ). Thus, the amount of Ni in soybean grains found in this study is considered safe and does not pose a threat to human health if direct consumption of grain is taking into account.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the experimental evidence reported previously. 26,27 The differentiation of osteoblasts was assessed via ALP activity, an early marker of osteoblast differentiation. 28 After 3 days of treatment, the ALP activity of MC3T3-E1 cells was low because the cells were still in the proliferation stage.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the important roles of estrogen in the differentiation of tooth-forming cells [25], polymorphisms in ESRα and ESRβ may influence the occurrence of DF. Although previous research has reported ESR allele frequencies in different populations [26][27][28], the role of ESR gene polymorphisms in relation to DF has been unclear. Thus, we subsequently hypothesized that ESR gene polymorphic variations would be associated with DF status.…”
mentioning
confidence: 99%